Magnetic Retrieval of Encapsulated Beta Cell Transplants from Diabetic Mice Using Dual‐Function MRI Visible and Retrievable Microcapsules. Issue 16 (5th March 2020) - Delcassian, Derfogail; Luzhansky, Igor; Spanoudaki, Virginia; Bochenek, Matthew; McGladrigan, Collin; Nguyen, Amy; Norcross, Samuel; Zhu, Yuhan; Shan, Crystal Shuo; Hausser, Reed; Shakesheff, Kevin M.; Langer, Robert; et al.
Abstract: Encapsulated beta cell transplantation offers a potential cure for a subset of diabetic patients. Once transplanted, beta cell grafts can help to restore glycemic control; however, locating and retrieving cells in the event of graft failure may pose a surgical challenge. Here, a dual‐function nanoparticle‐loaded hydrogel microcapsule is developed that enables graft retrieval under an applied magnetic field. Additionally, this system facilitates graft localization via magnetic resonance imaging (MRI), and graft isolation from the immune system. Iron oxide nanoparticles encapsulated within alginate hydrogel capsules containing viable islets are transplanted and the in vitro and in vivo retrieval of capsules containing nanoparticles functionalized with various ligands are compared. Capsules containing islets co‐encapsulated with COOH‐coated nanoparticles restore normal glycemia in immunocompetent diabetic mice for at least 6 weeks, can be visualized using MRI, and are retrievable in a magnetic field. Application of a magnetic field for 90 s via a magnetically assisted retrieval device facilitates rapid retrieval of up to 94% (±3.1%) of the transplant volume 24 h after surgical implantation. This strategy aids monitoring of cell‐capsule locations in vivo, facilitates graft removal at the end of the transplant lifetime, and may be applicable to many encapsulated cell transplant systems. Abstract : Magnetic hydrogel capsules containing iron oxide nanoparticles are developed for islet encapsulation. These capsules restore normal glycaemia and remain responsive to magnetic fields following transplant into diabetic mice. This enables MRI imaging of transplant grafts in vivo and facile surgical retrieval of transplants in applied magnetic fields. This system overcomes previous limitations in capsule tracking and retrieval post‐transplant.